ZOLMITRIPTAN BRAIN TARGETING VIA INTRANASAL ROUTE USING SOLID LIPID NANOPARTICLES FOR MIGRAINE THERAPY: FORMULATION, CHARACTERIZATION, IN-VITRO AND IN-VIVO ASSESSMENT - MOSTAFA, DALIA A. ELATY; KHALIFA, MAHA K. A.; GAD, SAMEH S. (International Journal of Applied Pharmaceutics, 2020)
Objective: Zolmitriptan, a class of antidepressant drugs with poor bioavailability due to its first-pass metabolism. The aim of this study was to improve systemic bioavailability and explore the brain targeting impact of nasal Zolmitriptan (Zol) solid lipid nanoparticles (SLNs) gel for migraine treatment. Methods: Stearic acid and cholesterol used as solid lipid and lecithin as a surfactant, emulsion solvent evaporation technique was used to produce Zolmitriptan SLNs. (Zol) SLNs were characterized for particle size, percent entrapment efficiency and in vitro drug release. Formula S6 showed greater percent entrapment efficiency (PEE), adequate particle size and sustained drug release behavior. Formula S6 was integrated into HPMC gel (3%) to prepare nasal gel. Zol SLN nasal gel was subjected to histopathological study to ensure brain targeting. Results: It was observed that all prepared Zol SLNs were in the nano-sized range with a polydispersity index of<0.5. In the cholesterol/lecithin combination, higher PEE%, better stability, and less agglomeration inclination were discovered. Results of the release profiles showed that developed Zol-SLNs were able to release Zolmitriptan in a sustained manner. Histopathological study of the brain tissues showed that Zolmitriptan SLN nasal gel can reach brain cells and localized for 24 h although the hydrophobicity of the target drug. Conclusion: Intranasal administration of Solid lipid nanostructure of Zolmitriptan through the olfactory pathway in which it travels from the nasal cavity to brain tissue achieved drug targeting potential of about 90% compared with conventional Zolmitriptan tablets. The small particle size helped them to squeeze themselves through the small opening in the olfactory neurons to the brain via different endo-cystic pathways of neuronal cells in nasal tissue membranes.